Bank Specific Risks and Financial Stability Nexus: Evidence From Pakistan - Chai, Zhengmeng; Sadiq, Muhammad Nauman; Ali, Najabat; Malik, Muhammad; Hamid, Syed Ali Raza (Frontiers in Psychology, 2022)
This article investigates the nexus between bank-specific risks and the financial stability of the banks in Pakistan. The SBP website is used to extract data for 15 scheduled banks in Pakistan over a 12-year period from 2009 to 2020. In the present study, we only used conventional banks and among these, excluded those banks that had some missing observations for the selected period. The study used the Hausman test to select a suitable model for study. Based on the Hausman test result, we used fixed effect model for study. Before conducting the Hausman test, study also conducted some diagnostic tests, such as multicollinearity analysis and heteroscedasticity test. The result shows that bank specific risks i.e. credit risk and liquidity risk have a negative impact on bank stability, whereas funding risk has no significant impact on bank stability. Beside these, bank size has also negative impact on bank stability. Whereas, ROA revealed a positive influence. These findings have several implications for policymakers and bank management in Pakistan. Bank management should establish policies that ensure secure loan granting and timely reimbursement from customers to minimize the credit risk. Besides this, management should keenly observe the liquidity position and should effectively mobilize the customer deposits to attain financial stability.